Model AC-Voltage Controller Using SVPWM Technique To Improve Power Quality :Case Study Dire Dawa National Cement Share Company - Ambessa, Sori (ASTU, 2019)
The Automatic Voltage Regulator (AVR) has more switching loss, voltage sag and Total Harmonics Distortion. This is an issue of industrial applications today in Dire Dawa National Cement Share Company (NCSC). The causes of the problems in the factory include sudden load changes, power system faults (short circuited) and reducing of its efficiency. In power electronic devices various Pulse-Width-Modulation (PWM) techniques have been developed for industrial applications. Out of the various methods, the Space Vector Pulse Width Modulation (SVPWM) based voltage control has established to the most versatile. It is providing better sinusoidal wave form of both voltages and currents, fast switching, less sags and total harmonic distortion. In this thesis works, using MATLAB R2013a Simulink software. AC-voltage controller using SVPWM techniques are analyzed, designed and simulated to reduce the sags and total harmonics that are dominant in NCSC of induction motor. The THD values of AVR and SVPWM are compared. The modeled THD values of current were highly reduced compared with the THD value measured from the company of the existing AVR controller in NCSC. This improves the power quality problems in this factory by adjusting the THD of voltage from 3.266% to 1.60%; and similarly THD of current from 33.2% to 1.27%.
Case Study Dire Dawa National Cement Share Company
Keywords: AVR, Power quality, SVPWM-AC controller, Voltage sag and Harmonics.